PENERAPAN MARKETING MIX UNIVERSITAS WIRARAJA DALAM UPAYA MENINGKATKAN MINAT MAHASISWA BARU - Nur Qoudri Wijaya (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2018)
The development of science and technology requires people to make the changes so that they can keep abreast of the times. The role of knowledge is significant for any society that wants to improve its ability to follow the competitive rivalry in the multidimensional crisis. Thus, Wiraraja University as a Higher Education institution has a task that is noteasy, it needs a good management system. This is so that educational institutions become one of the services in the field of education that has contributed to the development of the Nation and State. This research aims to analyzes the factors supporting and inhibiting factors as well as the concept of Marketing Mix to increase interest in new students at the University Wiraraja Sumenep. This research is descriptive quantitative research, the technique used in data collection are interviews, observation, Documentation and the questionnaire.The results of the group of dataare analyzed using methodsForce Field Analysis. Marketing Mix in the University Wiraraja in an effort to increase student interest in new approaches 7 P yaituProduct (products), Price (price), people (human resources), Place (location / place), Promotion (promotion), Physical Evidence (Physical Infrastructure) , Proces (Service) has not run optimally. Need for strategy development to increase interest in new students, skill soft equip the students, increased educational qualifications for lecturers, do not raise the cost of education, the provision of entrepreneurial provision for students. And to increase the number of new students is required new student recruitment agency aims to increase the number of new students.